Pengaruh Persepsi Kemudahan, Persepsi Manfaat, Promosi E-Wallet dan Lingkungan Teman Sebaya terhadap Perilaku Konsumtif Mahasiswa - Miswanto Miswanto; Putri Arneta Sidik; Mohamad Faiz Arrafi (Faculty of Economics and Business, Universitas Stikubank, 2021)
This study aims to examine the effect of perceived convenience, perceived benefits, e-wallet promotion, and peer environment on the consumer behavior of students using ShopeePay. The object of the research is students who use the ShopeePay e-wallet in various regions with primary data obtained from distributing questionnaires. The analytical method used is the convenience sampling method. The findings of this study indicate that (1) Perception of convenience does not have a positive effect on student consumptive behavior, (2) Perception of benefits does not have a positive effect on student consumptive behavior, (3) Promotion has a positive effect on student consumptive behavior, and (4) Peer environment has a positive effect on student consumptive behavior.